Frailty-driven burden of falls in older adults: a cross-sectional study estimating QALY loss and YLD in an urban Indian population - Surya Kannan; Jyotsna Deshmukh; Uday Narlawar; Amirtharaj Jaisankar; Disha Vatyani (International Journal Of Community Medicine And Public Health, 2026)
Background: Frailty is a multidimensional geriatric syndrome associated with increased vulnerability to adverse outcomes, particularly falls. Although both frailty and falls are common among older adults in India, their combined impact in terms of health loss remains inadequately quantified. This study aimed to estimate the burden of falls among frail and non-frail elderly using quality-adjusted life years (QALY) and years lived with disability (YLD). Methods: An analytical cross-sectional study was conducted among 200 adults aged ≥60 years in an urban field practice area attached to a tertiary care center in central India. Frailty was assessed using the Edmonton Frail Scale, quality of life using EQ-5D-5L (Indian value set), and fall-related disability using global burden of disease weights. Differences in QALY loss and YLD between frail and non-frail groups were analyzed using appropriate statistical tests, and multivariable linear regression was used to identify determinants of QALY loss. Results: The overall prevalence of falls was 28.0%, with a higher prevalence among frail individuals (46%) compared to non-frail (10%). Mean QALY loss was significantly higher among frail elderly (0.475±0.185) than non-frail (0.203±0.155; p